Parental Acceptance and Its Associated Factors Towards COVID-19 Vaccination among Elementary School Children: A Cross-Sectional Study in Bali, Indonesia - Swarjana, I Ketut; Darma Suyasa, I Gede Putu; Kusuma Negara, I Gusti Ngurah Made (YCAB Publisher, 2025)
Background: Efforts to control the transmission of coronavirus disease 2019 (COVID-19) and associated deaths continue, one of which is providing COVID-19 vaccination not only to adolescents, adults, and older adults but also to elementary school children. However, parental approval for the vaccination of the children is needed for the government’s vaccination program to succeed. Objectives: This study sought to determine parental acceptability of the COVID-19 vaccine and related factors for primary school-aged children in Bali, Indonesia. Methods: This cross-sectional study involved 420 respondents recruited through a multistage random sampling process. It collected data using a questionnaire shared through Google Forms. It analyzed the data using univariate, bivariate, and multivariate regression analyses. Results: Of the 420 respondents, 249 (59.3%) stated they accepted COVID-19 vaccination for elementary school students. Vaccine safety factors (adjusted odds ratio [AOR]: 14.376, 95% confidence interval [CI]: 7.682–26.903, p < 0.001), place of residence (AOR: 0.430; 95% CI: 0.271–0.683, p < 0.001), and history of comorbidities (AOR: 0.402, 95% CI: 0.222–0.726, p = 0.003) were significantly associated with parents’ approval of COVID-19 vaccination for elementary school children. Conclusion: Parents must be educated about vaccine safety, especially those living in cities and whose children have a history of comorbidities, to improve parental approval of COVID-19 vaccination according to the government’s target.